The interaction of human immunodeficiency virus-1 and human endogenous retroviruses in patients (primary cell cultures) and cell line models - Federica Mantovani; Konstantina Kitsou; Dimitrios Paraskevis; Pagona Lagiou; Gkikas Magiorkinis (Microbiology Spectrum, 2023)
ABSTRACT Human endogenous retroviruses (HERVs) integrated into the human genome millions of years ago, and their expression has been described both in healthy tissues and in pathology. In the present study, we study the differential expression of multiple HERV families in the presence of human immunodeficiency virus (HIV) infection in the peripheral blood mononuclear cells (PBMCs) of HIV-positive individuals, in HIV-infected cell lines, and in vitro HIV-infected macrophages/monocytes of healthy donors, utilizing publicly available data sets for secondary analysis using a pipeline appropriate for HERV transcription detection and comparison. We recognized significantly decreased expression of HERV-H in treatment-naïve HIV patients with viremia and increased expression of multiple HERV families in the PBMCs of HIV-infected individuals under combination antiretroviral therapy compared to healthy donors, in in vitro HIV-infected Stanford University pediatric T (SUP-T1) cells at 24 hours after HIV infection compared to non-infected SUP-T1 cells, and in in vitro HIV-infected MT4 T cells at 3 days after HIV infection compared to non-infected MT4 T cells. We recognized significantly increased expression of HERV-W, after HIV infection in monocyte-derived macrophage cell culture; no difference was found in HERV expression after HIV infection of monocyte cultures. We found a significantly decreased expression of HERV-K (HML-6) in donor-derived macrophage cultures at 36 hours after HIV infection, which does not persist at 6 days after infection. HIV infection modifies the expression of multiple HERV families in the PBMCs of HIV patients and in T cell-derived cultures, while the effect of HIV infection on HERV expression appears to be more restricted in cells of monocytic origin. IMPORTANCE In this work, we demonstrated that human immunodeficiency virus (HIV) infection leads to the modification of the human endogenous retrovirus (HERV) expression. Differential expression of multiple HERVs was found in peripheral blood mononuclear cells derived from HIV-infected patients compared to healthy donors and HIV-infected T cell cultures compared to non-infected. The effect of HIV presence on HERV expression appears to be more restricted in cells of monocytic origin, as only deregulation of HERV-W and HERV-K (HML-6) was found in these cell cultures after their infection with HIV. Multiple factors contribute to this aberrant HERV expression, and its levels appear to be modified in a time-dependent manner. Further studies and the development of optimized in vitro protocols are warranted to elucidate the interactions between HIV and HERVs in detail.